Tingkat Pengetahuan Penderita Hipertensi tentang Kepatuhan Berobat - Julio Fernandes; Mira Triharini; Eka Mishbahatul M. Has (Journal of Telenursing (JOTING), 2023)
This study aimed to determine the level of knowledge of hypertensive patients about medication adherence. The research method used is descriptive qualitative with a cross-sectional approach. The results showed that most of the 37 research samples were aged 51-65 years (59.4%), women (54.1%), a high education level (14%), self-employed (35.1%) stage two hypertension at the time of visit (86 .48%), many sufferers have a lack of knowledge (56.8%), and patients are not compliant in treatment (74.1%). In conclusion, most hypertension sufferers who seek treatment at the Internal Medicine Outpatient Unit at the Guido Valadares Nacional Hospital Dili Timor Leste have a poor level of knowledge, and most are also disobedient to their hypertension treatment. Keywords: Hypertension, Compliance, Level of Knowledge